Sarcoidosis and Corticosteroid Therapy: Dilemma from a Psychiatric Point of View - Mohd Amiruddin Mohd Kassim; Ruziana Masiran; Pang, Nicholas Tze Ping (Archives of Psychiatry Research, 2021)
Introduction and Methods: A man diagnosed with sarcoidosis developed partial retrograde amnesia followed by three months of depressive symptoms with panic attacks, which remitted with an antidepressant and a benzodiazepine. However, three months later hallucinations and overvalued persecutory ideations subsequently emerged, only to show partial response to antipsychotic treatment. Results: Sarcoidosis was treated with corticosteroids but serial thorax imaging shows minimal response. Corticosteroid was onboard throughout treatment, corresponding with non-remission of psychotic symptoms. There are persistent subjective cognitive difficulties but Mini Mental State Exam score is full. He is currently being treated with escitalopram, alprazolam and quetiapine. Conclusion: This case illustrated the dilemma between prolonging the corticosteroid therapy for sarcoidosis treatment and the psychiatric sequalae. While symptomatic antipsychotic treatment is effective, multi-disciplinary approach is imperative in determining the duration of the corticosteroid therapy.